2018
DOI: 10.1016/j.actatropica.2018.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Haemoproteus paraortalidum n. sp. in captive Black-fronted Piping-guans Aburria jacutinga (Galliformes, Cracidae): High prevalence in a population reintroduced into the wild

Abstract: Haemosporidian parasites of the genus Haemoproteus are widespread and can cause disease and even mortality in birds under natural and captive conditions. The Black-fronted Piping-guan (Aburria jacutinga) is an endangered Neotropical bird of the Cracidae (Galliformes) going through a reintroduction program to avoid extinction. We used microscopic examination and partial cytochrome b DNA sequencing to describe a new Haemoproteus species infecting Black-fronted Piping-guans bred and raised in captivity that were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…prevalence and vice versa. That same pattern has already been recorded in Amazonian birds (Svensson-Coelho et al 2013 ) and it could be indicative of vector host preferences, particularly since each genus is vectored by different dipteran insects (Ferreira-Junior et al 2018 ). Therefore, exposure rates could be also associated with bird behaviours (nesting type and height, social behaviour, foraging height, etc.)…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…prevalence and vice versa. That same pattern has already been recorded in Amazonian birds (Svensson-Coelho et al 2013 ) and it could be indicative of vector host preferences, particularly since each genus is vectored by different dipteran insects (Ferreira-Junior et al 2018 ). Therefore, exposure rates could be also associated with bird behaviours (nesting type and height, social behaviour, foraging height, etc.)…”
Section: Discussionsupporting
confidence: 77%
“…Other studies reported blood parasites on captive terrestrial birds, Cracidae: Aburria jacutinga ( Haemoproteus spp. ; 62.1%, 18/29) (Ferreira-Junior et al 2018 ), A. jacitinga (haemosporidians; 42.8%, 18/42) (Motta et al 2013 ), A. mantelli ( Plasmodium spp. ; 78.0%, 25/32) (Banda et al 2013 ), Mitu tormentosum ( Plasmodium spp.…”
Section: Discussionmentioning
confidence: 99%
“… H. paraortalidum (Fig. 17 j) [ 108 ] 18 (17) Fully grown gametocytes of roundish or various oval forms (Fig. 17 k, l) are present.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies addressed morphological and molecular characterization, distribution and genetic diversity of haemoproteids [ 14 20 ]. However, some bird groups remain insufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%